Ijtihad Siyasi dalam Perspektif Interaksionisme Simbolik sebagai Akar Komunikasi Politik Persatuan Islam - Hamzah Turmudi (Communicatus: Jurnal Ilmu komunikasi, 2020)
Islamic unity (Persatuan Islam) as an organization of Islamic society is seen as having its patterns and models of political communication that cannot be separated from the doctrine of understanding Islamic teachings with a vision of returning to the Qur'an and Sunnah. In some political momentum, Islamic Unity has the characteristics and mechanisms of political aspiration and participation as an effort to internalize fiqhiyyah puritanism. This refers to the nidzam jamiyyah (organizational rules) that have been agreed upon by the members of the Islamic Unity from the level of the Central Leadership, Regional Leaders, Regional Leaders, Branch Managers, and Jamaat Leaders. This article aims to explore the roots of political communication in the organization of Islamic Unity from the perspective of symbolic interactionism. The study was conducted using a qualitative approach through the study of phenomenology. Phenomenology is used to explore the tradition of the roots of political communication involving twelve members of the Bandung Islamic Association as the main informant. The results showed that the siyasi ijtihad was seen as the root of the political communication of Islamic Unity. Where ijtihad siyasi covers three main political communication strategies, namely idaratu da'wah as the Persian congregation's self-concept, idaratu quwwah as a Persis political communication framework and idaratu ummah as a Persis political communication society framework. The research implications show how ijtihad siyasi is interpreted as a fiqhiyyah reference in the framework of constructing the concept of proselytizing in the national field.Persatuan Islam sebagai sebuah organisasi masyarakat Islam dipandang memiliki pola dan model komunikasi politik tersendiri yang tidak bisa dilepaskan dari doktrin pemahaman ajaran Islam dengan visi kembali pada al-qur’an dan Sunnah. Dalam beberapa momentum politik, Persatuan Islam memiliki karakteristik dan mekanisme aspirasi dan partisipasi politik sebagai upaya internalisasi puritanisme fiqhiyyah. Hal ini merujuk kepada nidzam jamiyyah (aturan organisasi) yang telah disepakati oleh jamaah Persatuan Islam dari level Pimpinan Pusat, Pimpinan Wilayah, Pimpinan Daerah, Pimpinan Cabang dan Pimpinan Jamaah. Artikel ini bertujuan untuk menggali akar komunikasi politik pada organisasi Persatuan Islam dalam perspektif interaksionisme simbolik. Penelitian dilakukan dengan menggunakan pendekatan kualitatif melalui studi fenomenologi. Fenomenologi digunakan untuk menggali tradisi akar komunikasi politik yang melibatkan dua belas jamaah Persatuan Islam Kota Bandung sebagai informan utama. Hasil penelitian menunjukkan bahwa ijtihad siyasi dipandang sebagai akar komunikasi politik Persatuan Islam. Dimana ijtihad siyasi meliputi tiga strategi komunikasi politik utama, yakni idaratu da’wah sebagai konsep diri jamaah Persis, idaratu quwwah sebagai kerangka pikir komunikasi politik Persis dan idaratu ummah sebagai kerangka society komunikasi politik Persis. Implikasi penelitian menunjukkan bagaimana ijtihad siyasi dimaknai sebagai rujukan fiqhiyyah dalam kerangka membangun konsep dakwah Persis dalam medan kebangsaan.